Investigation of the Effects of Substituents and Various Solvents on UV-Visible Spectra of 5-(Quinolinylmethylene)barbituric Acid Derivatives - CANLICA, MEVLUDE; KERIM BEKER, H.; AKINCI, ALPER; KABAN, SENIZ (Asian Journal of Chemistry, 2010)
The effects of substituents and solvents on the UV-visible spectra of 5-(quinolinylmethylene)barbituric acid derivatives have been investigated.